ComAcc Card / Nur Syafiqah Hussin … [et al.] - Hussin, Nur Syafiqah; Awang, Naqiah; Najid, Nurul Afzan; Md Pauzi, Suria Fadhillah (Division of Research and Industry Linkages, 2017)
This study is directed towards the effectiveness of gamification intervention to the traditional teaching and learning methods among non-accounting students in higher education. This study is not rather to support a single approach in teaching and learning process but to study the effectiveness of the gamification as an intervention to the traditional method among non-accounting student in higher education. Gamification is expected to make students hooked by the idea of the game and make them engaged in the game's idea and activity, which eventually allowing the possibility of learning. The features of the game encourage curiosity and exploration to enhance engagement and improving content comprehension. At the end of the process the students will be rewarded with knowledge and skills that the game offered. The game called as ComAcc Card is triggered by the importance of students’ ability to memorize items for each component in accounting. Failure to do so will affect the process of preparation of financial statements, which is part of the course requirements. The game is expected to strengthen the students' ability to classify items according to its components in accounting. Thus, the study will compare performance of the students before and after the gamification intervention following the execution of traditional method in classroom.